The effect of dose escalation on gastric toxicity when treating lower oesophageal tumours: A radiobiological investigation - Carrington, R; Staffurth, J; Warren, S; Partridge, M; Hurt, C; Spezi, E; Gwynne, S; Hawkins, M; Crosby, T (BioMed Central, 2015)
Purpose: Using radiobiological modelling to estimate normal tissue toxicity, this study investigates the effects of dose escalation for concurrent chemoradiation therapy (CRT) in lower third oesophageal tumours on the stomach. Methods and materials: 10 patients with lower third oesophageal cancer were selected from the SCOPE 1 database (ISCRT47718479) with a mean planning target volume (PTV) of 348 cm3. The original 3D conformal plans (50Gy3D) were compared to newly created RapidArc plans of 50GyRA and 60GyRA, the latter using a simultaneous integrated boost (SIB) technique using a boost volume, PTV2. Dose-volume metrics and estimates of normal tissue complication probability (NTCP) were compared. Results: There was a significant increase in NTCP of the stomach wall when moving from the 50GyRA to the 60GyRA plans (11-17 %, Wilcoxon signed rank test, p = 0.01). There was a strong correlation between the NTCP values of the stomach wall and the volume of the stomach wall/PTV 1 and stomach wall/PTV2 overlap structures (R = 0.80 and R = 0.82 respectively) for the 60GyRA plans. Conclusion: Radiobiological modelling suggests that increasing the prescribed dose to 60Gy may be associated with a significantly increased risk of toxicity to the stomach. It is recommended that stomach toxicity be closely monitored when treating patients with lower third oesophageal tumours with 60Gy.